2020
DOI: 10.3389/fendo.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide Is a Potential Therapeutic Tool for Patients With Metastatic Pheochromocytoma/Paraganglioma—Case Report and Review of the Literature

Abstract: Context: Metastatic pheochromocytoma/paraganglioma (MPP) therapy mainly involves radionuclide therapy, chemotherapy, and targeted therapy. In recent years, temozolomide (TMZ) showed great promise in some MMP patients, especially those with SDHB germline mutation. We reported a patient with MPP who did not have any known germline genetic change and responded remarkably well to TMZ monotherapy.Case presentation: The patient was a 41-year-old woman with local and distant recurrence (soft tissues and bone metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Two small studies ( 19 , 20 ) and several case reports ( 23 ) have found temozolomide to be an effective chemotherapy in a number of patients with metastatic PPGL. Reported response to temozolomide was shown to be greater if the patient had a germline SDHB mutation ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two small studies ( 19 , 20 ) and several case reports ( 23 ) have found temozolomide to be an effective chemotherapy in a number of patients with metastatic PPGL. Reported response to temozolomide was shown to be greater if the patient had a germline SDHB mutation ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies reported on signs and symptoms in patients with mPPGLs, but comparative data including an appropriate group of patients without metastatic disease was also lacking [ 6 , 14 , 25 ]. Some studies, focusing on specific symptoms, found a higher proportion of patients with mPPGLs complaining of severe constipation compared to those without metastatic disease [ 26 28 ]. We could not confirm any difference in constipation between groups, though this complaint is likely associated with larger tumor burden and secretion of norepinephrine than in most of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is used in neuroendocrine tumors, both as monotherapy and in combination with capecitabine ( 86-89 ). Several case reports have demonstrated that temozolomide also may be active in metastatic PPGLs ( 90 , 91 ). In a consecutive retrospective study, 15 patients with PPGLs, among whom 10 (67%) had SDHB mutation, were treated with temozolomide (median dose 172 mg/m 2 ) daily for 5 days every 28 days ( 70 ).…”
Section: Treatmentmentioning
confidence: 99%